Generic characteristic of medium voltage reference network for the Malaysian power distribution system - Ibrahim K.A.B.; Au M.T.; Gan C.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Crashworthiness; Feeding; Local area networks; Sampling; Statistical methods; Distribution systems; Generic characteristics; Medium voltage networks; Power distribution system; Reference network; Stratification techniques; Stratified sampling; Voltage transformation; Complex networks